(Table 1) Boron analyses from ODP Sites 186-1150 and 186-1151 - Annette Deyhle; Achim J Kopf (PANGAEA, 2002)
Interstitial pore waters from Ocean Drilling Program (ODP) Sites 1150 and 1151, both penetrating ca. 1200 m of sub-seafloor sediment from the upper Japan Trench forearc, were analyzed for B concentrations and d11B isotopes. B concentrations cover a wide range from 329 to 3920 μM (0.8-9.3* seawater) and vary isotopically from +20 to +46 per mil (relative to SRM 951). In general, B concentrations increase more or less steadily with depth. At both sites, the B enrichment and isotopic changes seem to be related to a deep fluid influence, possibly coupled with alteration of volcanic products. Silica diagenesis does not affect the B geochemistry of the waters, as is evident from intact diatom tests and high opal-A contents throughout the holes. The B enrichment is more pronounced at Site 1150 in the seismic portion of the forearc. Here, a large positive anomaly in d11B values is observed, which corresponds with abundant fracturing and two prominent shear zones. At about the same depth range at Site 1151, the d11B values show a negative shift, attesting to an enrichment in 10B in the fluid as a result of B desorption from clay due to burial and tectonic stress. We conclude that B release from clay minerals is the major contributor to pore fluid anomalies, and that fluid flow through permeable out-of-sequence thrust (like the shear zones at Site 1150) may be an efficient mechanism for B backflux from the forearc into the hydrosphere.
Supplement to: Deyhle, A; Kopf, AJ (2002): Strong B enrichment and anomalous d11B in pore fluids from the Japan Trench forearc. Marine Geology, 183(1-4), 1-15, https://doi.org/10.1016/S0025-3227(02)00186-X